INTENSITY AND THE PROCESS OF PHOTORECEPTION - Hecht, Selig (The Rockefeller University Press, 1920)
1. In the photosensory process of Mya the latent period varies inversely as the intensity of the stimulating light. 2. Quantitative analysis of the data shows that the photochemical effect of the light is a logarithmic function of its intensity, the two variables being related to each other according to the well known "compound interest" law. 3. Comparison with previous experiments demonstrates that the Reciprocity Law of Bunsen and Roscoe applies to the photosensory process not only for the minimum energy required for a response, but for a much greater range of energy application as well.